Transforming Conventional Banking Contracts to Sharia-Compliant Systems in Aceh: Legal and Operational Challenges - Anna Sayyida Sya'bani (Postgraduate of Univeritas Islam Negeri Sunan Gunung Djati Bandung, 2024)
This study examines the transformation of conventional banking contracts into Sharia-compliant agreements following Qanun Aceh No. 11 of 2018. Aceh's financial institutions are required to transition to Islamic financial systems, employing Sharia-based mechanisms such as subrogation, qardh, and hiwalah to restructure contracts. Through document analysis and case studies, this research identifies both operational adjustments and legal challenges in implementing these changes. Results show that while existing methods facilitate the conversion process, further refinement is necessary to meet Sharia principles fully. This highlights the need for enhanced frameworks to support sustainable Islamic banking in Aceh.